SOCIAL ENABLEMENT ON ECONOMIC RECOVERY PROCESS OF SME’S SECTOR AT NEW NORMAL ERA IN KEDIRI CITY - Rahayu, Okta Yustin; Kriswibowo, Arimurti (Universitas 17 Agustus 1945 Surabaya, 2021)
The emergence of Covid-19 in Indonesia has caused a prolonged pandemic so that the economy in several regions has experienced drastic control. This is mainly felt by business actors including local SME entrepreneurs. In the third quarter of 2020 the President issued a Presidential Decree regarding the new adaptation habits Kediri City Government was ready for post-pandemic economic recovery through community empowerment based on community empowerment, most of the SME programs in economic development led the government to issue economic policies to create an efficient economic business climate for the community. The purpose of this research is to find the effectiveness of the steps taken by the Kediri City Government through community based enablement (CBE) as a solution to the socio-economic recovery of society in the era of adaptation to new habits and to answer the challenges of the Government and the SME community in efforts to restore the community perspective based on empowerment in communities. Kediri City. The method used is descriptive qualitative research. From this research it can be seen that Kediri City in carrying out post-pandemic economic recovery with a community-based empowerment approach effectively returns the market to the eyes of consumer SMEs through digital marketing and SME malls which are made as a forum for digital buyer and seller interactions and train people to be able to develop innovation products and take decisions independently so that they do not receive guarantees from the Government and can run independently through understanding and training provided previously.